(untitled) (Екологічний вісник Криворіжжя, 2025)
Modern education is undergoing transformation due to digitalization and integration of new technologies, one of the key factors is the development of artificial intelligence (AI) and neural networks, which are actively introduced into the educational process. This is especially true of natural sciences, where large volumes of data are analyzed, modeling and forecasting play a critical role. Information technologies, in particular artificial intelligence (AI) and neural networks, play a key role in the transformation of natural education. The article considers the concept of iterative development of neural networks and their impact on the methods of teaching the discipline of the natural cycle. Also, the possibilities of applying AI in biology, physics, chemistry, geography, ecology, agricultural sciences and medicine are analyzed. The impact of AI on natural education is significant and the result is transformative. Due to adaptability, the possibilities of automation and individualization of learning, AI opens up new opportunities for improving the quality of education. However, at the same time, important ethical issues related to the use of AI are involved, in particular, in the context of privacy and preserving the role of the teacher. Further development of AI in education requires a thoughtful approach to maintain a balance between technological achievements and human values, which are the basis of the educational process.